"Isn't There Any Other Way than Calling the Cops?": How Differences in Initiation of Police Intervention Influence Survivor Safety. Issue 23 (December 2022) - Nnawulezi, Nkiru; Engleton, Jasmine; Jumarali, Selima; Royson, Samantha; Murphy, Christopher
As formal crisis responders, police are trained in de-escalation tactics that are expected to mitigate intimate partner violence and promote survivor safety. However, the alignment between expected and actual practice of police intervention varies, especially when the survivor does not initiate the call, police treat the survivor poorly, or provide an undesirable arrest outcome. At best, unsuccessful interventions do not change survivors' risk level, and at worse, elevate their risk of experiencing harm. The purpose of this qualitative study was to explore survivors' perspectives on the process of police intervention, specifically how variations in initiation, quality of engagement, and arrest influence survivors' safety. Twenty-four women whose partners were in a relationship violence intervention program were recruited to participate in the study. Results showed that many survivors described a range of ongoing, strategic violence perpetrated by their partners that required intervention; yet the complex nature of the violence often extended beyond police capacity. Either survivors called the police, or they were initiated externally by neighbors or strangers; some survivors had dual initiations. Whether survivors reported that police used safety practices during the intervention was related to who initiated the police. Arrests of abusive partners were inconsistent, and they varied based on number of previous calls to the police and visible signs of injury. Survivors of color, specifically Black women, self-initiated at higher rates, experienced fewer safety strategies used by police, and had fewer arrests. No matter the outcomes of police intervention, survivors actively engaged in strategies outside of formal systems to protect themselves and their families. Study results imply that police intervention may be ill-suited to support survivors' safety goals and highlight a need for alternative interventions focused on de-escalation and prevention.